2021
DOI: 10.1002/smll.202007671
|View full text |Cite
|
Sign up to set email alerts
|

Nanochemistry Modulates Intracellular Decomposition Routes of S‐Nitrosothiol Modified Silica‐Based Nanoparticles

Abstract: Cellular delivery of nitric oxide (NO) using NO donor moieties such as S‐nitrosothiol (SNO) is of great interest for various applications. However, understandings of the intracellular decomposition routes of SNO toward either NO or ammonia (NH3) production are surprisingly scarce. Herein, the first report of SNO modified mesoporous organosilica nanoparticles with tetrasulfide bonds for enhanced intracellular NO delivery, ≈10 times higher than a commercial NO donor, is presented. The tetrasulfide chemistry modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…[126] SNO GSH-responsive NO release NO induces apoptosis in cancer cells. [131] Arg 808 nm laser-activated IR783 transfers its energy or electron to oxygen to generate ROS dominantly composed of 1 O 2 that induces release of NO from l-Arg…”
Section: Nonoatementioning
confidence: 99%
See 1 more Smart Citation
“…[126] SNO GSH-responsive NO release NO induces apoptosis in cancer cells. [131] Arg 808 nm laser-activated IR783 transfers its energy or electron to oxygen to generate ROS dominantly composed of 1 O 2 that induces release of NO from l-Arg…”
Section: Nonoatementioning
confidence: 99%
“…Yu et al prepared tetrasulfide bond-containing dendritic mesoporous SiO 2 nanoparticles, with modified SNO on the surface (DMON-SNO). [131] The tetrasulfide bridging group oxidizes the high concentration of GSH in tumor cells into oxidized glutathione (GSSG). Due to the retention of GSH by the tetrasulfide bridging group, DMON-SNO shifts the reaction to NO release and reduces NH 3 production.…”
Section: 𝛼-Cd-conjugated No Prodrug (𝛼-Cd-no) and Ce6 (𝛼-Cd-ce6mentioning
confidence: 99%
“…[9,10] Immunotherapy utilizes patients' own immune systems to identify and destroy cancer cells, often with high specificity and low toxicity to eradicate primary tumors, inhibit metastasis, and prevent recurrence. [11][12][13][14][15][16] Among immunotherapy methods, artificial cancer vaccines have attracted extensive attention for their longterm immune responses, a vital factor for cancer therapy. [17,18] However, individual differences may lead to limited therapeutic effectiveness, thus limiting the clinical application of artificial cancer vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…36 For example, tetrasulfide-bridged silica nanoparticles have been demonstrated to deliver cargo in GSH-rich cell types. 4,37,38 Herein, we report the repurposed application of Pio for CAF reprogramming using an organosilica-based nano-delivery platform. Dendritic mesoporous organosilica nanoparticles (DMONs) with a tetrasulfide bridging group loaded with pioglitazone (DMON-P) have been prepared.…”
mentioning
confidence: 99%
“…According to previous research, CAFs have been observed to possess increased levels of intracellular glutathione (GSH), which can be used as an intracellular cue for the responsive release of cargo . For example, tetrasulfide-bridged silica nanoparticles have been demonstrated to deliver cargo in GSH-rich cell types. ,, …”
mentioning
confidence: 99%